A rigid-flexible coordinated method to control weld residual stress and deformation during local PWHT for ultra-large pressure vessels. (June 2021) - Jin, Qiang; Jiang, Wenchun; Wang, Chengcai; Yang, Zhongwei; Luo, Yun; Yan, Guizhen; Tu, Shan-Tung; He, Yinbiao
Abstract: Local post welding heat treatment (PWHT) is a feasible method to eliminate weld residual stress for ultra-large pressure vessels. This paper is focused on the discussion of weld residual stress and deformation for the typical ultra-large mechanical penetration inserted plate (MPIP) during the local PWHT. The reason why the MPIP subjected to local PWHT causes cracking is clarified. A rigid-flexible coordinated control method is proposed to prevent cracking during local PWHT for the ultra-large pressure vessels. The results show that the inconsistent deformation and greater stress concentration in weld toe are the main reason to result in cracking during PWHT. The axial stresses and radial deformation in the welded joints can be reduced by the rigid-flexible coordinated control method. The axial stress is changed to compressive stress, and the radial deformation is reduced by about 58%. And the inconsistent deformation in welded joints during the heat treatment can be obviously improved, which is of great significance to ensure the safe service for ultra-large pressure vessels. Graphical abstract: Image 1 Highlights: The greater stress concentration induced by bend deformation is the main reason of cracking. A rigid-flexible coordinated method was proposed to avoid cracking during local PWHT. The axial stress and radial deformation in weld during PWHT were improved by new method. The inconsistent and maximum deformation at insulation stage can be improved greatly. The smooth weld can reduce the risk to occur cracking during local PWHT.